Aktivitas Ekstrak Averrhoa bilimbi, Annona squamosa, dan Tithonia diversifolia terhadap Mortalitas dan Penghambatan Pertumbuhan Larva Crocidolomia pavonana (Lepidoptera: Crambidae) - Kusuma Tuti, Harlina; Dadang; Sri Ratna, Endang (Jurnal Hortikultura Indonesia, 2019)
Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) is one of the important insect pests that can reduce production of cruciferous plants. Generally farmers control this insect pest by using synthetic insecticides. However, the intensive and excessive use of synthetic insecticides may cause negative impact to the insect and environment, such as the occurence of resistance and resurgence of pests and chemical residues in agricultural products. One of alternative strategies that can be adopted to reduce the negative impact of synthetic insecticide use is by utilization of botanical insecticide. The aim of this research was to study the activities of extract Averrhoa bilimbi leaves, Annona squamosa seeds, and Tithonia diversifolia flowers on mortality and growth inhibition of C. pavonana larvae. The mortality activity was assessed by single and extract mixture using leaf residual method. The larval growth inhibition activity was also tested by using leaf residual method. A. squamosa extract at concentration of 0.015% could kill 100% of larvae at 72 hours after treatment (HAT). Meanwhile, T. diversifolia extract at 5% could kill 88% of larvae at 144 HAT. Extract mixtures of T. diversifolia and A. squamosa at ratios 1:1, 1:2 and 2:1 (w/w) gave low mortality activity. These three extract showed growth inhibition activity against the larvae of C. pavonana.Keywords: Botanical insecticides, cabbage pest, extract mixture, toxicity